Altered Lipid Profile in Patients with Gallstones admitted for Cholecystectomy (Medical Forum Monthly, 2024)
Background: The cholesterol content is important in classifying gallstones as either cholesterol or pigment stones. Most of the gallstones are cholesterol stones. There is a multifactorial and complex relationship between blood cholesterol, Low Density Lipoprotein, and High Density Lipoprotein levels and cholesterol gallstone formation. Evidence showed that more than half of patients with gallstones have altered serum lipids which are a risk factor for ischemic heart diseases.Objective: This study was done to find out frequency of altered lipid profile in patients with gallstones admitted for cholecystectomy at Dow University Hospital Karachi Pakistan.Study Design: case series study.Place and Duration of Study: This study was conducted at the Surgical Unit-2, Dow University Hospital, OJHA Campus, Karachi for a period of 14 months from January 2012 to March 2013.Materials and Methods: All diagnosed patients of cholelithiasis were included in this case series study. Lipid profile was performed for all patients before performing cholecystectomy. Post operatively gallbladder specimens were sent for histopathology and stones for chemical analysis.Results: A total number of 45 patients were included in this study, out of which 40 were female. The mean age of patients was 47.7 ± 13.3 years. On chemical analysis, Cholesterol was found in all of the stones. The histopathology of all patients showed chronic cholecystitis. The total mean serum cholesterol level was 199.3 ± 36.8 , HDL cholesterol was 43.5 ± 7.7, LDL ± 23.9 cholesterol was 127.2 ± 23.9, and triglycerides were 139.1 ± 37.5. Serum total cholesterol was elevated in 28/45 patients (62.2%), LDL cholesterol was elevated in 26/45 (57.7%), triglycerides elevated in 18/45(40.0 %,) whereas HDL cholesterol was below normal in 16/45 (35.5%) of patients.Conclusion: Most of the patients operated for Lap Cholecystectomy had altered lipid profile. Patients presenting with Cholelithiasis should be investigated for altered lipid profile, which is a major risk factor for developing cardiovascular disease if left untreated.